Vitamin D supplementation, its role and impact in athletes and recovery after physical exercise: Narrative review - Łukasz Kołodyński; Gabriela Kubicka; Wiktoria Sobocinska (Polish Journal of Sports Medicine, 2026)
Background. Vitamin D is a pleiotropic hormone involved not only in bone mineralization and calcium-phosphate metabolism but also in muscle function, immunity, cardiovascular health, and athletic performance. Deficiency is common among athletes and may impair recovery, strength, and resistance to infections. This narrative review aimed to review and analyze the current literature on the role of vitamin D supplementation and its impact on athletic performance, post-exercise recovery, and athletes’ health.Material and methods. A literature review was conducted using PubMed, Google Scholar, and ResearchGate databases. Studies concerning biochemical mechanisms, ergogenic effects, supplementation protocols, and safety of vitamin D in athletes were analyzed using the keywords: vitamin D, muscle recovery, vitamin D in sports, and vitamin D supplementation. Results. Vitamin D influences skeletal muscle through genomic and non-genomic pathways, supporting muscle growth, regeneration, and contraction. Supplementation has been associated with improved muscle strength, reduced fracture risk, and better bone health in athletes. Vitamin D also modulates immune function by reducing pro-inflammatory cytokines and lowering susceptibility to respiratory infections. Additionally, evidence suggests beneficial effects on cardiovascular and pulmonary function. Deficiency was frequently observed in athletic populations, particularly during winter.Conclusions. Vitamin D is essential for musculoskeletal health, immune regulation, cardiovascular and respiratory function, and athletic performance. Routine monitoring of serum 25-hydroxyvitamin D levels and individualized supplementation strategies should be considered in athlete care.